Military education for non-military purposes: Economic and social governing projects targeting conscripts in early twentieth-century Sweden. Issue 1 (5th June 2017) - Sundevall, Fia
Abstract : Purpose: The purpose of this paper is to explore military service-linked economic and social governing initiatives in early twentieth-century Sweden, and thereby offer a broadened understanding of educational institutions as governing arenas. Design/methodology/approach: Using the term "governing" to describe and analyse various calculated techniques of the state – and/or affiliated governing actors – to influence and direct the behaviour of conscripts in order to deal with particular economic and/or social problems, the author ask what kind of economic and social problems policymakers and social commentators of education were looking to deal with, why military service was considered a suitable means and/or setting for doing so, and what governing techniques they proposed be used. The author furthermore take in consideration the intimate links between citizenship, gender, and military service and argue that the governing initiatives analysed enables us to understand these links in partly new and a more concrete way. Findings: The study shows that there were numerous ideas and requests amongst policymakers and social commentators of education on making use of the nation's conscription scheme for non-military purposes as it provided the nation with a unique opportunity to reach and influence entire generations of men on the threshold of adulthood. Proposals included, e.g., the use of various forms of instruction in assorted subjects, facilitation of base libraries and an extension of the period of military service, in order to deal with economic and social problems such as, e.g., mass unemployment, alcohol abuse, elementary education deficiencies, and uneducated voters, as well as shortages of skilled personnel in particular branches of great importance for the nation's economy. Originality/value: While there is a sizable and growing body of research on governing initiatives in non-military educational settings, proposed and implemented to solve various economic and social problems in society, scholars in Sweden and elsewhere have largely overlooked the use and role of military service in such undertakings. This paper seeks to redress the balance and thereby offers a broadened understanding of educational institutions as governing arenas.